Imelda's day in court ; The politics of Lahar ; Fr. Rogliardi [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Tackles Imelda Marcos conviction in court for ill-gotten wealth; debate on the lahar scam; and interview with Fr. Pierre Rogliardi, parish priest in Las Pinas, about his program to provide decent housing for the poor in his community.